Прогресування інсулінорезистентності у вагітних жінок за наявності ожиріння I та II ступенів тяжкості сполучається з надмірною продукцією лептину та С-реактивного білку - Тарасенко, К.В. (Таврический медико-биологический вестник, 2013)
У 36 беременных с ожирением І и ІІ степени тяжести (основная группа) и у 21 беременной с нормальной массой тела (контрольная группа) во ІІ триместре беременности исследовали показатель инсулинорезистентности – индекс НОМА, содержание лептина и биомаркеры системного воспаления (туморнекротический фактор-альфа, С-реактивный белок) с помощью иммуноферментного анализа. Установлено, что у беременных с сопутствующим ожирением инсулинорезистентность прогрессирует в зависимости от увеличения массы тела и сочетается с повышением содержания лептина и развитием системного воспаления. Using immunoenzymatic analysis, the insulin resistance index – the Homeostasis Model Assessment (HOMA), leptin concentrations and biomarkers of systemic inflammation (tumor necrosis a-factor, C-reactive protein) have been investigated in a group of pregnant women with concomitant class I and class II obesity (36 women) and in a group of those with the normal body mass (21 women), in the second trimester of pregnancy. It has been found that in pregnant women with concomitant obesity the insulin resistance progresses with the body mass increase and is combined with the leptin concentration increase and development of systemic inflammation.